Pengaruh Pembiayaan Murabahah terhadap Kinerja Keuangan Bank Syariah di Indonesia - Nugraha, Adhi; Jaya, Hendra; Judi Ichwan (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2023)
This study aims to analyze the impact of murabahah financing on the financial performance of Islamic banks in Indonesia. Murabahah financing is one of the main products of Islamic banks, contributing significantly to overall financing. Financial performance is measured using profitability ratios such as Return on Assets (ROA) and Return on Equity (ROE). The data used in this study were obtained from the financial statements of Islamic banks registered with the Financial Services Authority (OJK) during the 2017–2022 period. The results indicate that murabahah financing has a significant positive effect on the financial performance of Islamic banks. These findings highlight the importance of optimizing murabahah financing to enhance the competitiveness of Islamic banks in Indonesia